Reductive evolution in outer membrane protein biogenesis has not compromised cell surface complexity in Helicobacter pylori - Webb, Chaille T.; Chandrapala, Dilini; Oslan, Siti Nurbaya; Bamert, Rebecca S.; Grinter, Rhys D.; Dunstan, Rhys A.; Gorrell, Rebecca J.; Song, Jiangning; Strugnell, Richard A.; Lithgow, Trevor; Kwok, Terry (John Wiley & Sons, 2017)
Helicobacter pylori is a gram-negative bacterial pathogen that chronically inhabits the human stomach. To survive and maintain advantage, it has evolved unique host-pathogen interactions mediated by Helicobacter-specific proteins in the bacterial outer membrane. These outer membrane proteins (OMPs) are anchored to the cell surface via a C-terminal β-barrel domain, which requires their assembly by the β-barrel assembly machinery (BAM). Here we have assessed the complexity of the OMP C-terminal β-barrel domains employed by H. pylori, and characterized the H. pyloriBAM complex. Around 50 Helicobacter-specific OMPs were assessed with predictive structural algorithms. The data suggest that H. pylori utilizes a unique β-barrel architecture that might constitute H. pylori-specific Type V secretions system. The structural and functional diversity in these proteins is encompassed by their extramembrane domains. Bioinformatic and biochemical characterization suggests that the low β-barrel-complexity requires only minimalist assembly machinery. The H. pylori proteins BamA and BamD associate to form a BAM complex, with features of BamA enabling an oligomerization that might represent a mechanism by which a minimalist BAM complex forms a larger, sophisticated machinery capable of servicing the outer membrane proteome of H. pylori.